2019
DOI: 10.2967/jnumed.119.233155
|View full text |Cite
|
Sign up to set email alerts
|

Label-Free Visualization of Early Cancer Hepatic Micrometastasis and Intraoperative Image-Guided Surgery by Photoacoustic Imaging

Abstract: The detection of cancer micrometastasis for early diagnosis and treatment poses a great challenge for conventional imaging techniques. The aim of our study was to evaluate the performance of photoacoustic imaging (PAI) in detecting hepatic micrometastases from melanoma at a very early stage and in aiding tumor resection by intraoperative guidance. Methods: In vivo studies were performed by following protocols approved by the Ethical Committee for Animal Research at Xiamen University. First, a mouse model of B1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(48 citation statements)
references
References 39 publications
0
48
0
Order By: Relevance
“…In addition, we found that the tumour, when artificially located in deep tissue, could be clearly imaged and discriminated with a depth of up to 5 mm. A previous study reported the application of PAI with endogenous melanin as contrast for the resection of B16 melanoma liver metastasis [30]. Hepatic melanoma in vivo as small as 400 µm could be detected at a depth of up to 7 mm and precisely resected using PAI guidance, demonstrating the advantages of PA (i.e., high resolution, high sensitivity, deep penetration and early detection of hepatic micrometastasis).…”
Section: Discussionmentioning
confidence: 90%
“…In addition, we found that the tumour, when artificially located in deep tissue, could be clearly imaged and discriminated with a depth of up to 5 mm. A previous study reported the application of PAI with endogenous melanin as contrast for the resection of B16 melanoma liver metastasis [30]. Hepatic melanoma in vivo as small as 400 µm could be detected at a depth of up to 7 mm and precisely resected using PAI guidance, demonstrating the advantages of PA (i.e., high resolution, high sensitivity, deep penetration and early detection of hepatic micrometastasis).…”
Section: Discussionmentioning
confidence: 90%
“…Further studies are needed in order to confirm our data in a larger sample and to assess the influence of any technical problem. New imaging tools and techniques will probably make easier in the future the diagnosis of malignancy in case of subcutaneous masses [35,36].…”
Section: Discussionmentioning
confidence: 99%
“…Lv et al studied the application of in vivo photoacoustic imaging in the dynamic monitoring of the early stages of ischemic stroke and proposed a highly sensitive in vivo photoacoustic imaging model [4]. Qian et al proposed a guided surgery method based on photoacoustic imaging to achieve tumor resection [5]. Lu et al proposed a photoacoustic contrast agent based on functional peptide-modified gold nanoparticles for the problems of the photoacoustic imaging of bacterial infections [6].…”
Section: High-frequency Acoustic Signal In Cell Photoacoustic Detectionmentioning
confidence: 99%